Broken Glass: The Social Evil of Urban Poverty and a Critical Education. Issue 7 (November 2019) - Wheeler-Bell, Quentin
Ghettos are a social evil. They are social atrocities maintained by inexcusable racist laws and practices, structures of class domination, and institutionalized political marginalization. After Brown v. The Board of Education, educational reformers have increasingly (mis)framed the problem of "ghetto schools" as a failure to provide urban youth with the social and cultural capital to integrate into mainstream society. This integrationist approach is insufficient because it inadequately addresses the social evil of ghetto poverty. Instead, I argue, a critical education approach is morally more appropriate because it focuses on giving children the tools for transforming capitalism and racial domination.